Causes and impacts of flooding towards the flood victims in Taman Sri Muda, Shah Alam, Selangor / Nur Arisha Iliyana Othman and Asniza Hamimi Abdul Tharim - Othman, Nur Arisha Iliyana; Abdul Tharim, Asniza Hamimi (2023)
Floods are the most significant natural disasters which affect many people and inflict damage worth several million every year in Malaysia. Unfortunately, in December 2021, the nation experienced a heartbreaking episode of floods across eight states, including the area of Shah Alam, Selangor. Shah Alam is disposed to flood when heavy rainfall occurs, leading to extensive damage and disruptions for its residents. Effective flood relief management is crucial to mitigate the damages, ensure the safety and well-being of residents, and facilitate a swift recovery process. The aim of the paper is to explore and assess the perceptions of residents in Shah Alam, Selangor, regarding issues, causes, and impacts of flooding, with the goal of providing valuable insights to the authorities. The research methodology used in this research was the quantitative method, specifically the observation method questionnaire method. The study consists of a questionnaire survey, a survey of residents' perceptions of various agencies, and an analysis of the data gathered. The results show the recognition of residents toward issues arising, causes and impacts of flooding toward residents. The data analysis reveals causes of flooding which are natural factors and human factors while impact of flooding which are individual, communities and economic factors. The findings will help the authority to take further action in improving and enhancing our country’s flood management will increase the resilience of the country, minimise flood-related damages, and develop the overall safety and well-being of its residents.